2010
DOI: 10.2340/16501977-0550
|View full text |Cite
|
Sign up to set email alerts
|

Development of a tool for prediction of falls in rehabilitation settings (Predict_FIRST): A prospective cohort study

Abstract: This tool provides a simple way to quantify the probability with which an individual patient will fall during a rehabilitation stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 28 publications
1
62
0
2
Order By: Relevance
“…Knee bends may be a meaningful FP screening test that justifies further studies of physical performance related to the risk of falls. Designing prospective cohort studies therefore seems to be justified (Sherrington et al, 2010;Sai et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Knee bends may be a meaningful FP screening test that justifies further studies of physical performance related to the risk of falls. Designing prospective cohort studies therefore seems to be justified (Sherrington et al, 2010;Sai et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The tandem stance and high force tests of the lower limbs, such as chair rises or knee bends as well as grip strength were considered to be risk predictors for falls (Ensrud et al, 2009;Sherrington et al, 2010). We assumed deployment of force in a shorter time (higher power) to better help avert falling after stumbling.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple falls or fall injuries risk factors, such as demographic status, socioeconomic characteristics, and health status, in community-dwelling older adults were identified in previous studies (Harwood, 2001;Krueger, Brazil, & Lohfeld, 2001;Sherrington et al, 2010;Steinman, Pynoos, & Nguyen, 2009;Unsworth & Mode, 2003). However, being affected by the uncertainty associated with diverse study design and subject resource, the findings vary from different studies with regard to some factors.…”
Section: Introductionmentioning
confidence: 85%
“…The person is asked to stand up and sit down from a chair five times as quickly as possible with their arms folded. Previous studies have shown that performance on the 5STS is associated with reduced lower-extremity muscle strength [8,9] , impaired balance [9][10][11] , reduced reaction time and psychological factors such as pain and vitality [9] . Studies have shown that the 5STS performance is slower in frailer populations and people with balance disorders [12] .…”
Section: Introductionmentioning
confidence: 99%